Multisectoral aspirations for food systems governance and the enduring dominance of agriculture - Anna K. Farmery; Rebecca Campbell; Andre Flores; Senoveva Mauli; Dori Patay; Acacio Sarmento; Anja Bless; Federico Davila; Fiona Berry; Alisi Tuqa (Frontiers in Sustainable Food Systems)
Transforming food systems to be healthier, more sustainable and more equitable will require coordinated efforts across diverse sectors. The agricultural sector typically dominates food system governance, potentially risking imbalance in the food systems space and sustaining an emphasis on food availability and agricultural production over more integrated solutions to food system challenges. We examine contemporary food systems governance, with a focus on the UN Food Systems Summit (UNFSS) and on the Pacific and East and Southeast Asian regions. We reflect on the implications of agricultural dominance in the food system space and identify opportunities to support multisectoral food system governance to facilitate positive food system change.